Paroxysmal nocturnal hemoglobinuria: the path to diagnosis - E. F. Makhnyr; N. O. Inasaridze (Klinicist)
The aim of study was to describe the case of diagnosis of orphan disease — paroxysmal nocturnal hemoglobinuria in clinical practice of the therapist on an outpatient basis.Materials and methods. The patient Sh., 47 years, due to the gradual increase in the volume of the abdomen, the appearance of swelling of the legs, the increase in shortness of breath, yellowing of the skin, the appearance of rare but abundant nosebleeds appealed to 63polyclinic N. I. Pirogov City Clinical Hospital № 1. The patient was repeatedly hospitalized. During the diagnostic search, additional research methods were carried out: evaluation of laboratory data in dynamics; x-ray of the abdominal cavity; ultrasound examination of the abdominal cavity, kidneys and retroperitoneal space; computed tomography of the abdominal cavity; ultrasound examination of the pelvic organs; liver biopsy followed by microscopic examination of micro-drugs; samples for the diagnosis of autoimmune diseases; immunophenotyping of peripheral blood. The patient was consulted by a surgeon, hematologist.Results. In the course of difficult verification of such rare pathology, diagnostic and therapeutic concepts changed. The patient underwent symptomatic treatment: drainage of the abdominal cavity with evacuation of more than 14 liters of ascitic fluid; therapy with fresh frozen plasma; plasmapheresis. And only after positive clinical and laboratory dynamics during therapy with Eculizumab, immunophenotypic diagnosis was performed, that showed erythrocytes of type I (normal expression of CD59) — 1.2 %, type III (complete deficiency of CD59) — 49.5 %; monocytes with FLAER/CD14 deficiency — 83.4 %; granulocytes with FLAER/CD24 deficiency — 77.77 %. On the basis of these results, the diagnosis of paroxysmal nocturnal hemoglobinuria was established. Taking into account the severe course of the disease, according to vital indications, the patient continues therapy with Eculizumab at a maintenance dose of1200 mg every 14 (± 2) days.Conclusion. Timely highly qualified diagnosis, a modern approach in the treatment of this disease, provided a satisfactory outcome of the process in the patient with improved clinical condition and a favorable prognosis for health.